Mathematical Model of Automatic Control System for Asynchronous Multimotor Drive - Issenov, S. S. (Elektronika ir Elektrotechnika, 2012)
The work contains the findings of the application of the finite automata theory that resulted in the development of mathematical models of automated control system for the asynchronous multimotor drive using Mealy apparatus. The work also proposes how to vividly describe the sequence of logical operations - underlying the creation of a programming language - of a digital control device with the use of an algorithm language and Boolean algebra for the automated operation of a microprocessor device, which allows raising the level of automatization of the asynchronous multimotor drive control system. DOI: http://dx.doi.org/10.5755/j01.eee.18.8.2602